Individual and psychological factors influencing hotel employee’s work engagement: The contingent role of self-efficacy - Hussam Al Halbusi (14492861) (2023)
This study intended to examine the relationships between empowerment leadership, psychological empowerment, and affective commitment on work engagement. Importantly, this study aimed to examine the moderating role of self-efficacy on the relationship between psychological empowerment and affective commitment on work engagement. The data were collected in a two-waves week time lag, data was gained from 375 full-time front-line employees working in five-star hotels in Erbil. The structural equation modelling (SEM) using partial least squares (PLS) was used to analyze the research model. Thus, our results indicated that empowerment leadership is positively related to psychological empowerment, and affective commitment as well as psychological empowerment, and affective commitment were found to be significantly related to work engagement. Self-efficacy was a vital moderator in the relation of psychological empowerment, and affective commitment toward work engagement such as the relationship is stronger when self-efficacy is high than low. This study provides theoretical and managerial implications such as having to empower leadership in the workplace because it provides a sustainable competitive advantage to organizations as well as limitations and future research directions. This study, like every study, has limitations. To begin with, the responses were confined to front-line employees working in five-star hotels, thus the findings cannot be applied to employees working in other types of hotels in the hotel industry. The managerial implication is this study has shown the importance of having empowering leadership in the workplace because it provides a sustainable competitive advantage to organizations. In suggestions to initiate empowerment leadership, hotels should hire and train leaders who are willing to empower their subordinates how to empower their subordinates. Other Information Published in: Cogent Business & Management License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/23311975.2023.2254914 Additional institutions affiliated with: University of Derby, UK - Qatar